Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa - Isna Zuhaira; Mukhtar Mukhtar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This is the result of a study that aims to evaluate the improvement of students' mathematical problem-solving abilities at MTs Kesuma LKMD using the Student Team Achievement Divisions (STAD) cooperative learning model. The subjects of this study were grade VIII students of MTs LKMD Jati Kesuma in the even semester of the 2021/2022 academic year, with a total of 28 students consisting of 12 male students and 16 female students. The assessment instruments used were Observation Sheets, Tests and Documentation. This research is a Classroom Action Research (CAR) which consists of the stages of planning, implementing actions, observation, and reflection. CAR is carried out collaboratively, where researchers work together with grade VII mathematics teachers of MTs Kesuma LKMD with the material of the Two Variable Linear Equation System (SPLDV) to improve students' mathematical problem-solving abilities with learning completeness reaching 70%. In cycle I, the average score of class VIII-a in the mathematical problem-solving ability test was 58.33, which increased to 73.45 in cycle II, resulting in an increase of 15.12 points. This increase is reflected in each indicator of mathematical problem-solving ability from cycle I to cycle II.